Poria cocos Wolf extracts represses pigmentation in vitro and in vivo - Lee, HyunKyung; Cha, Hwa Jun (Cellular and Molecular Biology, 2018)
In skin, melanocytes determine skin color using melanogenesis, which induces protective mechanism to oxidative stress and UV damage. However, when melanin is excessive produced by the various stimulus, the accumulated melanin induces hyperpigmentation disease such as melasma, freckles, Melanism ware induced. Therefore, it is implicated to finding potential agents for whitening to be used in cosmetic products. In our present study, we show that Poria cocos Wolf extracts decreased melanin synthesis in B16F10. And then this inhibition of melanogenesis was provoked by regulation of tyrosinase activity and tyrosinase and MITF expression. Moreover, Poria cocos Wolf extracts contained cream improved skin tone using increase of bright value. Overall, these results provide evidence to potential agent for whitening to be used in cosmetic products.